2011
DOI: 10.1093/ejo/cjq156
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of space closure rates between preactivated nickel-titanium and titanium-molybdenum alloy T-loops: a randomized controlled clinical trial

Abstract: The purpose of this study was to conduct a prospective randomized controlled clinical trial to evaluate the rate of space closure and tooth angulation during maxillary canine retraction using preactivated T-loops made from titanium-molybdenum alloy (TMA) and nickel-titanium (NiTi). Twelve patients (six males and six females) aged between 13 and 20 years who had upper premolar extractions were included, and each acted as their own control, with a NiTi T-loop allocated to one quadrant and TMA to the other using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 21 publications
2
45
1
Order By: Relevance
“…This was expected since it has already been shown that betatitanium T-loops produced with larger wire sizes produced more force. 18 The NiTi T-loops previously shown in the literature produced lower force levels [10][11][12] than was found in our study but were probably adequate for canine retraction. This study, however, aimed to evaluate springs for en masse retraction, where a force twice as large is generally suggested.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This was expected since it has already been shown that betatitanium T-loops produced with larger wire sizes produced more force. 18 The NiTi T-loops previously shown in the literature produced lower force levels [10][11][12] than was found in our study but were probably adequate for canine retraction. This study, however, aimed to evaluate springs for en masse retraction, where a force twice as large is generally suggested.…”
Section: Discussionsupporting
confidence: 48%
“…Even though the use of NiTi T-loops has already been shown in attempts to maintain the force upon deactivation, [9][10][11][12] it appears that they were designed for canine retraction. Because recent studies have shown that there is no difference in the rates of anterior retraction and loss of anchorage between that and en masse retraction, [13][14][15] it makes sense that the latter method would be clinically more practical and save chair time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En masse retraction studies have traditionally evaluated rates of tooth movement in vivo, relying on cephalometric measurements 10,11 and dental cast measurements 12,13 with applied forces being measured via force gauges. 14 Due to the inherent difficulty in accurate force measurements in vivo, studies using in vitro or numerical methods are considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, a high loop may irritate oral structures. Accordingly this is prudent to measure the load components produced by different design parameters of loops (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%